Molecular Mechanism of Action of Trimethylangelicin Derivatives as CFTR Modulators - Laselva, Onofrio; Marzaro, Giovanni; Vaccarin, Christian; Lampronti, Ilaria; Tamanini, Anna; Lippi, Giuseppe; Gambari, Roberto; Cabrini, Giulio; Bear, Christine E.; Chilin, Adriana; Dechecchi, Maria C. (Frontiers in Pharmacology, 2018)
The psoralen-related compound, 4,6,4’-trimethylangelicin (TMA) potentiates the cAMP/PKA-dependent activation of WT-CFTR and rescues F508del-CFTR-dependent chloride secretion in both primary and secondary airway cells homozygous for the F508del mutation. We recently demonstrated that TMA, like Lumacaftor (VX-809), stabilizes the first membrane-spanning domain (MSD1) and enhances the interface between NBD1 and ICL4 (MSD2). TMA also demonstrated anti-inflammatory properties, via reduction of IL-8 expression, thus making TMA a promising agent for treatment of Cystic Fibrosis. Unfortunately, TMA was also found to display potential phototoxicity and mutagenicity, despite the fact that photo-reactivity is absent when the compound is not directly irradiated with UVA light. Due to concerns about these toxic effects, new TMA analogues, characterized by identical or better activity profiles and minimized or reduced side effects, were synthesized by modifying specific structural features on the TMA scaffold, thus generating compounds with no mutagenicity and phototoxicity. Among these compounds, we found TMA analogues which maintained the potentiation activity of CFTR in FRT-YFP-G551D cells. Nanomolar concentrations of these analogues significantly rescued F508del CFTR-dependent chloride efflux in FRT-YFP-F508del cells, HEK-293 and CF bronchial epithelial cells. We then investigated the ability of TMA analogues to enhance the stable expression of varying CFTR truncation mutants in HEK-293 cells, with the aim of studying the mechanism of their corrector activity. Not surprisingly, MSD1 was the smallest domain stabilized by TMA analogues, as previously observed for TMA. Moreover, we found that TMA analogues were not effective on F508del-CFTR protein which was already stabilized by a second-site mutation at the NBD1-ICL4 interface. Altogether, our findings demonstrate that these TMA analogues mediate correction by modifying MSD1 and indirectly stabilizing the interface between NBD1 and CL4.